2022
DOI: 10.24136/oc.2022.011
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth and labour market in the European Union: lessons from COVID-19

Abstract: Research background: The world has been fighting the new pandemic caused by COVID-19 since March 2020. The subsequent restrictions on economic activity resulted in a supply shock, accompanied by a supply chain disruption, job layoffs, reduced work time and wages and decreased disposable incomes and taxes, which led to a demand shock. However, whether a close link exists between the number of confirmed cases, deaths and economic indicators during the COVID-19 pandemic remains uncertain. Purpose of the article: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 93 publications
2
24
0
Order By: Relevance
“…Developed cyberspace contributed to a large number of scientific studies devoted to the search for factors and determinants of the reciprocal relationship between the digitalization of social relations and social development (Vinska & Tokar, 2021;Omran & Bilan, 2022). In (Mishchuk, et al, 2019), this relationship is explored through in the light of social inequality; in (Privara, 2022, Virak & Bilan, 2022, in the light of potential disparities in the labor market. A study (Csordás, et al, 2020) found a significant relationship between digital competence and unemployment rates, as well as a positive correlation between digital competence and corporate training rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Developed cyberspace contributed to a large number of scientific studies devoted to the search for factors and determinants of the reciprocal relationship between the digitalization of social relations and social development (Vinska & Tokar, 2021;Omran & Bilan, 2022). In (Mishchuk, et al, 2019), this relationship is explored through in the light of social inequality; in (Privara, 2022, Virak & Bilan, 2022, in the light of potential disparities in the labor market. A study (Csordás, et al, 2020) found a significant relationship between digital competence and unemployment rates, as well as a positive correlation between digital competence and corporate training rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The efficacy of a code of ethics as a tool for managing the external and internal relations of an organisation is, however, not "automatic" (Singh, 2011;Ruiz-Lozano & Rios Berjillos Lara, 2016;Privara, 2022Privara, , 2022a. Efficacy is based on a number of prerequisites relating to contents, form, methods of creation, use and application, enforcement, etc.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Many scientists (Zhang et al, 2022;Sardak et al, 2018) development. Privara (2022) revealed that the number of cases of COVID-19 did not significantly damage the country's socioeconomic parameters, while mortality from the coronavirus disease dramatically negatively affected the country's economic development. Numerous researchers (Castro, 2022;Kuzior, Mańka-Szulik, Krawczyk, 2021;Alabdullah, Asmar, 2022;Dvorský et al, 2021;Capolupo, Palumbo, Adinolfi, 2022) identified the changes in the organizational and functional patterns of business models due to COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%